The Influence of Profitability and Corporate Social Responsibility on Company Value - Nastiti Rizky Shiyammurti; Jejen Jaenudin; Budi Prasetiyo; Rony Wardhana; Hera Nurfaidah (CV. Civiliza Publishing, 2025)
This study aims to test and analyze the influence of profitability and corporate social responsibility (CSR) on the value of companies in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the period 2018–2024. Profitability in this study was proxied by Return on Assets (ROA), while corporate social responsibility was measured using the Corporate Social Disclosure Index (CSDI). This study uses a quantitative approach with secondary data obtained from the company's financial statements and annual reports. The research sample consisted of 20 state-owned companies selected through purposive sampling techniques. The analysis method used was multiple linear regression with a significance level of 0.05 and data processing was carried out using the SPSS program. The results of the analysis showed that the value of the determination coefficient (R²) was 40.3%, which means that the variables of profitability and corporate social responsibility were able to explain the variation in company value by 40.3%, while the rest was explained by other variables outside the research model. The results of partial hypothesis testing showed that profitability had a significant effect on company value and corporate social responsibility also had a significant effect on company value. In addition, the results of simultaneous testing showed that profitability and corporate social responsibility together had a significant effect on the corporate value of state-owned companies listed on the Indonesia Stock Exchange, which was indicated by a significance level of less than 0.05.